Through the eyes of community health workers: what was needed to increase COVID-19 vaccine uptake in the Missouri Southeast region - Ban, Anusha; Shrestha, Ashish; Van den Berk-Clark, Carissa; Ballard, Janice; Logan, Richard; Logan, Tripp; Francioni, Anne; Murray, Megan; Baker, Elizabeth A. (Frontiers in Public Health, 2024)
Public health emergencies, such as the COVID-19 pandemic, elucidate the strengths, weaknesses and significant gaps in infrastructure, compatibility and consistency in communication systems and messaging, quality of collaborative relationships and regional collaboration, funding priorities and resource allocation, as well as provider and workforce capacity. They also expose longstanding patterns of mistrust in the government and healthcare systems, and inadequacy in socio-economic infrastructures. These issues resulted in higher COVID-19 infection and mortality rates, and lower vaccination rates in many rural counties across the nation, including Missouri. In response to these challenges, the COVID-19 Response Network was formed in the Southeast corner of Missouri. The Network was a community-academic partnership that brought together community and faith-based leaders, academicians, healthcare providers and administrators, public health practitioners, and pharmacists to facilitate collaboration on education and outreach efforts aimed at reducing vaccine inequity in the 16-county project area.Importantly, the Network also included Community Health Workers (CHWs) who worked with these different agencies and organizations and were at the heart of implementing Network activities. Qualitative methods, including in-depth interviews, were used to explore the professional and personal experiences of CHWs working at the grassroots level during an ongoing pandemic. Narrative analysis revealed effective communication and engagement strategies for increasing vaccine uptake in rural communities. For instance, fear-based messaging was perceived as coercive and met with resistance. In contrast, messages that shared personal experiences and catered to the human need to protect their loved ones were more effective. Trust in the source of information was critical. This study highlights the significance of exploring and leveraging the capacities of trusted community members like CHWs to increase the effectiveness of public health interventions in rural communities.